Wind-Tunnel Studies on Sand Sedimentation Around Wind-Break Walls of Lanxin High-Speed Railway II and Its Prevention - Hongchao Dun (Applied Sciences, 2021)
Wind-break walls along Lanxin High-Speed Railway II were studied and approved as effective measures to reduce strong wind damage to the high-speed trains. The results show that sand sedimentation on the leeward sides of wind-break walls along the railway within Gobi Desert could significantly threaten the operation safety of running trains. Different from the current sand sedimentation prevention measures without adequate consideration of the deposition process of airborne sand particles, this study revealed the mechanism of sand sedimentation on the leeward sides of three wind-break walls within different terrains. A series of wind-tunnel experiments were carried out to measure the horizontal velocity, number density, transport flux, and deposition rate of sand particles, and it was found that the horizontal speed of sand particles was first increased and then decreased on the railway track, and the peak speed over the concave subgrade was much smaller than those over convex and flat subgrades. The number density and horizontal sand flux were largest over the concave subgrade, and were the smallest over the convex subgrade. The sand particle deposition rate and distribution were also the largest within the concave subgrade, and some measures were also proposed to prevent sand sedimentation on the leeward sides of wind-break walls.